The inhibition of lung cancer cell migration by AhR-regulated autophagy - Tsai, Chi-Hao (Sci Rep, 2017)
The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that is highly expressed in multiple organs and tissues. Whereas AhR mediates the metabolism of xenobiotic and endogenous compounds, its novel function in cancer epithelial-mesenchymal transition (EMT) remains controversial. Autophagy also participates in tumour progression through its functions in cell homeostasis and facilitates adaptation to EMT progression. In the present study, we found that AhR-regulated autophagy positively modulates EMT in non-small cell lung cancer cells. The motility of A549, H1299, and CL1-5 cells were correlated with different AhR expression levels. Invasive potential and cell morphology also changed when AhR protein expression was altered. Moreover, AhR levels exerted a contrasting effect on autophagy potential. Autophagy was higher in CL1-5 and H1299 cells with lower AhR levels than in A549 cells. Both AhR overexpression and autophagy inhibition decreased CL1-5 metastasis in vivo. Furthermore, AhR promoted BNIP3 ubiquitination for proteasomal degradation. AhR silencing in A549 cells also reduced BNIP3 ubiquitination. Taken together, these results provide a novel insight into the cross-linking between AhR and autophagy, we addressed the mechanistic BNIP3 modulation by endogenous AhR, which affect cancer cell EMT progression.